2017
DOI: 10.1002/jcb.26184
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitogen Activated Protein Kinase and Maturation Promoting Factor During the Achievement of Meiotic Competency in Mammalian Oocytes

Abstract: The oocyte quality remains as one of the major problems associated with poor in vitro fertilization (IVF) rate and assisted reproductive technology (ART) failure worldwide. The oocyte quality is dependent on its meiotic maturation that begins inside the follicular microenvironment and gets completed at the time of ovulation in most of the mammalian species. Follicular oocytes are arrested at diplotene stage of first meiotic prophase. The resumption of meiosis from diplotene arrest, progression through metaphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…Similarly, increase of Thr-14/Tyr-15 and decrease of Thr-161 phosphorylated Cdk1 level resulted in EM-II and thereby abortive SEA in rat [5][6][7] and mouse eggs [37,38] cultured in vitro. The modulation of Cdk1 specific phosphorylation status could induce cyclin B1 dissociation and degradation [33][34][35][36][37][38]. Our results suggested that cyclin B1 level decreased significantly during EM-II ( Figure 2D2) as compared to control eggs ( Figure 2D1) and further supported by CTCF analysis (Figure 2D3; p < 0.001).…”
Section: Rosmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, increase of Thr-14/Tyr-15 and decrease of Thr-161 phosphorylated Cdk1 level resulted in EM-II and thereby abortive SEA in rat [5][6][7] and mouse eggs [37,38] cultured in vitro. The modulation of Cdk1 specific phosphorylation status could induce cyclin B1 dissociation and degradation [33][34][35][36][37][38]. Our results suggested that cyclin B1 level decreased significantly during EM-II ( Figure 2D2) as compared to control eggs ( Figure 2D1) and further supported by CTCF analysis (Figure 2D3; p < 0.001).…”
Section: Rosmentioning
confidence: 54%
“…i.e., cyclin-dependent kinase 1 (Cdk1) and a regulatory subunit, i.e., cyclin B1 [6,7,33,34]. However, changes in Cdk1 activity as well as MPF destabilization may also occur due to increase of mitogen-activated protein kinase (MAPK) [35]. This statement is supported by the observations that MAPK modulates Cdk1 activity and destabilizes MPF during spontaneous exit from M-II arrest [22,23].…”
Section: Resultsmentioning
confidence: 92%
“…Studies suggest that several enzymes, factors and signal molecules are involved during cell cycle progression from M‐I to M‐II stage and formation as well as extrusion of PB‐I that enable an oocyte to get converted into a good quality ovum (Miao, Kikuchi, Sun, & Schatten, ). The quality of ovum directly impacts the reproductive as well as ART outcome (Prasad, Tiwariet al, ; Tiwari et al, ; Tiwari, Tripathi, & Chaube, ). This review article focuses and updates the information on molecular and cellular changes during journey of oocyte from M‐I to M‐II stage and extrusion of PB‐I in mammalian oocytes (Figure).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular interactions through several pathways result in sub cellular as well as cellular changes during meiotic cell cycle progression from M‐I to M‐II stage in mammalian species. The cytostatic factors (CSFs) regulate maturation promoting factor (MPF) activity and modulate oocyte meiosis in rats (Tiwari & Chaube, ; Tiwari et al, ). MPF activity is high at M‐I stage and drops during meiotic exit from M‐I but increases at M‐II arrest in mouse oocytes (Terret et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation